The predictability and magnitude of life‐history divergence to ecological agents of selection: a meta‐analysis in livebearing fishes. (15th February 2016) - Moore, Michael P.; Riesch, Rüdiger; Martin, Ryan A.
Abstract: Environments causing variation in age‐specific mortality – ecological agents of selection – mediate the evolution of reproductive life‐history traits. However, the relative magnitude of life‐history divergence across selective agents, whether divergence in response to specific selective agents is consistent across taxa and whether it occurs as predicted by theory, remains largely unexplored. We evaluated divergence in offspring size, offspring number, and the trade‐off between these traits using a meta‐analysis in livebearing fishes (Poeciliidae). Life‐history divergence was consistent and predictable to some (predation, hydrogen sulphide) but not all (density, food limitation, salinity) selective agents. In contrast, magnitudes of divergence among selective agents were similar. Finally, there was a negative, asymmetric relationship between offspring‐number and offspring‐size divergence, suggesting greater costs of increasing offspring size than number. Ultimately, these results provide strong evidence for predictable and consistent patterns of reproductive life‐history divergence and highlight the importance of comparing phenotypic divergence across species and ecological selective agents.